2012
DOI: 10.1128/aac.06299-11
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Clinical Characteristics and Outcomes Associated with Vancomycin-Resistant Enterococcus faecalis and Vancomycin-Resistant E. faecium Bacteremia

Abstract: eIn published studies, cohorts of patients with bacteremia due to vancomycin-resistant Enterococcus (VRE) have predominantly been infected with Enterococcus faecium. Little is known about the epidemiology and outcomes associated with bacteremia due to VR Enterococcus faecalis. A retrospective study of isolates obtained from January 2008 to October 2010 was conducted at Detroit Medical Center (DMC). Unique patients with blood cultures positive for VRE were reviewed. Outcomes were analyzed using logistic regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 26 publications
1
32
0
1
Order By: Relevance
“…Exposure to cephalosporins was reported as a VRE risk factor in past studies, although none of these studies evaluated VR E. faecalis exclusively (16,17). We recently reported that patients with bacteremia due to VR E. faecalis were exposed to cephalosporins more frequently than were patients with VR E. faecium bacteremia (18). Fluoroquinolones were also independently associated with isolation of VR E. faecalis, and this association was demonstrated by other investigators with regard to VRE (16).…”
Section: Discussionmentioning
confidence: 73%
“…Exposure to cephalosporins was reported as a VRE risk factor in past studies, although none of these studies evaluated VR E. faecalis exclusively (16,17). We recently reported that patients with bacteremia due to VR E. faecalis were exposed to cephalosporins more frequently than were patients with VR E. faecium bacteremia (18). Fluoroquinolones were also independently associated with isolation of VR E. faecalis, and this association was demonstrated by other investigators with regard to VRE (16).…”
Section: Discussionmentioning
confidence: 73%
“…nterococci are facultative anaerobic Gram-positive cocci that exist as a major component of normal colonic flora and represent the third most common type of health care-associated pathogen in the United States (1,2). Although enterococci possess intrinsic resistance to several antibiotics, they have acquired additional resistance determinants, such as that for vancomycin resistance (3,4).…”
mentioning
confidence: 99%
“…Such comparisons have not been previously performed. We previously reported that VR E. faecalis bacteremia was independently associated with decreased in-hospital mortality compared to VR E. faecium (20). In this study, patients with VR E. faecalis bacteremia also had decreased in-hospital mortality compared to that of VR E. faecium (n ϭ 18 cases [20.9%] versus n ϭ 46 cases [33.1%], P ϭ 0.07).…”
Section: Discussionmentioning
confidence: 48%